2015
DOI: 10.1007/s10551-015-2596-2
|View full text |Cite
|
Sign up to set email alerts
|

Word Power: The Impact of Negative Media Coverage on Disciplining Corporate Pollution

Abstract: Sequences of individual words make up media reports. And sequences of media reports constitute the power of the news media to influence corporate practices. In this paper, we focus on the micro-foundations of news reports to elaborate how an atmosphere of negative news reports following an initial exposure of corporate pollution activity can help stop such activity through their impact on corporate managers. We extend our understanding of the corporate governance effect of news media by considering two new asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 68 publications
0
45
0
Order By: Relevance
“…This study employs legitimacy theory to examine whether a firm's dissemination of carbon‐related information ( iCarbon ) on Twitter's social media network can influence a firm's COE. Social media is an essential tool for connecting stakeholders with firms, for influencing corporate practice, and for controlling corporate pollution and irresponsible practices (Jia, Tong, Viswanath, & Zhang, ). The Twitter platform, which enables the isolation of the effect of dissemination from that of disclosure (Blankespoor et al, ; Jung, Naughton, Tahoun, & Wang, ), has “changed the disclosure landscape and the way firms communicate important information to stakeholders” (Lee, Hutton, & Shu, , p. 368) and can provide positive signals to market participants about a firm's environmental responsibility to respond to the uncertainty of carbon risks and to improve the firm's reputation and image (Barnett & Salomon, ).…”
Section: Introductionmentioning
confidence: 99%
“…This study employs legitimacy theory to examine whether a firm's dissemination of carbon‐related information ( iCarbon ) on Twitter's social media network can influence a firm's COE. Social media is an essential tool for connecting stakeholders with firms, for influencing corporate practice, and for controlling corporate pollution and irresponsible practices (Jia, Tong, Viswanath, & Zhang, ). The Twitter platform, which enables the isolation of the effect of dissemination from that of disclosure (Blankespoor et al, ; Jung, Naughton, Tahoun, & Wang, ), has “changed the disclosure landscape and the way firms communicate important information to stakeholders” (Lee, Hutton, & Shu, , p. 368) and can provide positive signals to market participants about a firm's environmental responsibility to respond to the uncertainty of carbon risks and to improve the firm's reputation and image (Barnett & Salomon, ).…”
Section: Introductionmentioning
confidence: 99%
“…They conclude that "CEO hubris significantly leads to more firm pollution" (2020, p. 474). Because firm pollution bears severe negative consequences (e.g., Heft-Neal et al 2018;Li et al 2019;Waller 2018), their study is highly relevant and worth noting carefully (e.g., Jia et al 2016;Li and Zhou 2017). Drawing on the author's regression analyses (see their Tables 4, 5, and 6), however, we question their central conclusion and the inferences made.…”
Section: Introductionmentioning
confidence: 94%
“…Previous experience in climate change has shown the influences of media on practices, politics, and public opinion and understanding related to climate change [54]. Another study indicated that the more negative the media coverage and the more local this coverage, the greater the impact of discipling corporate pollutions [55]. Recently, a group of scholars from South Africa have highlighted the issues of equity and inequality in the "pivot" to remote teaching and learning [56].…”
Section: Research Questionmentioning
confidence: 99%